Development of Employability Skills of Vocational School Students in Bogor, Indonesia - Arga Satrio Prabowo; Ahmad Yunus; Widiastuti Pajarini; Raudah Zaimah Dalimunthe; Putri Dian Dia Conia; Siti Aminah Alfalathi (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Career development is one of the important things that need to be done at every level of education so that students gain career maturity. One of the components in developing career maturity is Employability skills. Employability skills are a set of skills that are important for individuals to have to survive in a job. Vocational Schools in Indonesia, commonly called SMK, aim to graduate individuals ready to work. Therefore, SMK graduate needs to master employability skills. This study aimed to determine the effect of the employability skills program on vocational school students. The research was conducted at a state vocational school at Bogor with a weak experimental method and involved six students as samples. The research results indicate that the employability skills program can improve the employability skills of vocational students. This research implies that employability skills training can be applied in schools to help students master employability skills.